2004
DOI: 10.3748/wjg.v10.i6.919
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and management of patients with early acute severe pancreatitis: Experience from a medical center in China

Abstract: AIM:To study clinical characteristics and management of patients with early severe acute pancreatitis (ESAP). METHODS:Data of 297 patients with severe acute pancreatitis (SAP) admitted to our hospital within 72 h after onset of symptoms from January 1991 to June 2003 were reviewed for the occurrence and development of early severe acute pancreatitis (ESAP). ESAP was defined as presence of organ dysfunction within 72 h after onset of symptoms. Sixtynine patients had ESAP, 228 patients without organ dysfunction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 27 publications
(27 reference statements)
2
39
0
3
Order By: Relevance
“…We also observed significant improvement in Marshall score and MODS of patients with resolution of IAH. The overall mortality rate in our study of approximately 23% is comparable to the 10%-50% reported in AP patients by others [18][19][20][21] . The mortality in ACS patients in our study (75%), however, was much higher than that in patients without ACS which is not acceptable for us, although post-injury ACS has been consistently reported to have a high mortality ranging from 25%-75%.…”
Section: Discussionsupporting
confidence: 75%
“…We also observed significant improvement in Marshall score and MODS of patients with resolution of IAH. The overall mortality rate in our study of approximately 23% is comparable to the 10%-50% reported in AP patients by others [18][19][20][21] . The mortality in ACS patients in our study (75%), however, was much higher than that in patients without ACS which is not acceptable for us, although post-injury ACS has been consistently reported to have a high mortality ranging from 25%-75%.…”
Section: Discussionsupporting
confidence: 75%
“…Although older literature suggested that 80% of deaths occur after several weeks of illness as a result of infected necrosis, more recent surveys have shown considerable variation with several reports showing a reasonably even distribution of early deaths (within 1-2 wk) versus later deaths (46,72,76,150,151,163), a few showing the majority of deaths within the first 2 wk (67,75), and others showing the majority of deaths after the first 2 wk (59,89,135). These variations reflect a variety of influences including percentage of very ill patients referred to a reporting hospital compared to patients admitted directly.…”
Section: Overview Of Acute Pancreatitismentioning
confidence: 99%
“…However, severe acute pancreatitis is still characterized by rapidly progressive multiple organ failure and high mortality, and both surgical and conservative therapies yield poor outcomes [31] . Thus, most emphasis is placed on preventing the progression to multiple organ failure [32,33] . Congestive heart failure was more common in VRP patients than in PRRF patients and was a good prognostic predictor for ICU mortality in patients with VRP.…”
Section: Discussionmentioning
confidence: 99%